Molecular characterization of the Salmonella enterica serovar Typhi Vi-typing bacteriophage E1. - Pickard, D; Thomson, N; Baker, S; Wain, J; Pardo, M; Goulding, D; Hamlin, N; Choudhary, J; Threfall, J; Dougan, G (2008)
Some bacteriophages target potentially pathogenic bacteria by exploiting surface-associated virulence factors as receptors. For example, phage have been identified that exhibit specificity for Vi capsule producing Salmonella enterica serovar Typhi. Here we have characterized the Vi-associated E1-typing bacteriophage using a number of molecular approaches. The absolute requirement for Vi capsule expression for infectivity was demonstrated using different Vi-negative S. enterica derivatives. The phage particles were shown to have an icosahedral head and a long noncontractile tail structure. The genome is 45,362 bp in length with defined capsid and tail regions that exhibit significant homology to the S. enterica transducing phage ES18. Mass spectrometry was used to confirm the presence of a number of hypothetical proteins in the Vi phage E1 particle and demonstrate that a number of phage proteins are modified posttranslationally. The genome of the Vi phage E1 is significantly related to other bacteriophages belonging to the same serovar Typhi phage-typing set, and we demonstrate a role for phage DNA modification in determining host specificity.